Emerging precision diagnostics in advanced cutaneous squamous cell carcinoma - Glenn Geidel; Isabel Heidrich; Julian Kött; Stefan W. Schneider; Klaus Pantel; Christoffer Gebhardt (npj Precision Oncology, 2022)
Abstract Advanced cutaneous squamous cell carcinoma (cSCC) encompasses unresectable and metastatic disease. Although immune checkpoint inhibition has been approved for this entity recently, a considerable proportion of cases is associated with significant morbidity and mortality. Clinical, histopathological, and radiological criteria are used for current diagnostics, classification, and therapeutic decision-making. The identification of complex molecular biomarkers to accurately stratify patients is a not yet accomplished requirement to further shift current diagnostics and care to a personalized precision medicine. This article highlights new insights into the mutational profile of cSCC, summarizes current diagnostic and therapeutic standards, and discusses emerging diagnostic approaches with emphasis on liquid biopsy and tumor tissue-based analyses.